Clinicopathological factors relating malignant lymphoma with Sjogren's syndrome (1996)
This study was undertaken to summarize the current status of the clinicopathologicfactors related to non-Hodgkin's lymphoma (NHL) development in patients with Sjögren's syndrome (SS). Through a MEDLINE search, pertinent articles on SS, monoclonality, and NHL were found and reviewed. Malignant lymphoma description was based on the International Lymphoma Study Group classification. Patients with SS are known to have an increased risk for developing B-cell NHL (B-NHL). However, such a complication occurs in less than 10% of patients, being reported mainly in those with primary SS. Extranodal low-grade B-NHL are observed most frequently. Persistent enlargement of parotid glands, adenopathy, monoclonal gammopathy, and crossreactive idiotypes are all signs suggesting possible lymphoma evolution. Although monoclonality does not mean malignancy unequivocally, it is considered to be a precursor for NHL development in SS. Factors implicated into lymphomagenesis in SS include dysregulation in the mechanisms leading to apoptosis, hyperstimulation of B-1 cells, and an infectious agent. Polyclonal lymphoproliferation characterizing SS might in some instances transform into monoclonal, and then to malignancy. Further studies on the mechanism whereby NHL develops in SS are warranted.